Bioprinting-By-Design of Hydrogel-Based Biomaterials for In Situ Skin Tissue Engineering - Alisa Douglas; Yufei Chen; Margarita Elloso; Adam Levschuk; Marc G. Jeschke (Gels)
Burns are one of the most common trauma injuries worldwide and have detrimental effects on the entire body. However, the current standard of care is autologous split thickness skin grafts (STSGs), which induces additional injuries to the patient. Therefore, the development of alternative treatments to replace traditional STSGs is critical, and bioprinting could be the future of burn care. Specifically, in situ bioprinting offers several advantages in clinical applications compared to conventional in vitro bioprinting, primarily due to its ability to deposit bioink directly onto the wound. This review provides an in-depth discussion of the aspects involved in in situ bioprinting for skin regeneration, including crosslinking mechanisms, properties of natural and synthetic hydrogel-based bioinks, various in situ bioprinting methods, and the clinical translation of in situ bioprinting. The current limitations of in situ bioprinting is the ideal combination of bioink and printing mechanism to allow multi-material dispensing or to produce well-orchestrated constructs in a timely manner in clinical settings. However, extensive ongoing research is focused on addressing these challenges, and they do not diminish the significant potential of in situ bioprinting for skin regeneration.